THE EFFECT OF COMPETENCE AND CAREER ON EMPLOYEE PERFORMANCE AT THE PKS PTPN V SEI GARO KAMPAR REGENCY - Muhammad Fadel; Zamhir Basem; Henrizal Henrizal (Jurnal Riset Manajemen Indonesia, 2020)
Research to determine the effect of competence and career on employee performance with simulthan and partial at the PKS PTPN V Sei Garo Kampar Regency. Types and sources of data used in this study are primary data and secondary data, while data collection techniques used in this study were questionnaires, file research, observation and interviews. The population in this research were all employee at the PMKS PT. PKS PTPN V Sei Garo Kampar Regency in 2020, amounting to 94 employee and based on the Slovin formula it is know that the number of samples in this study is 48 employee at the PMKS PT. PKS PTPN V Sei Garo Kampar Regency. The sample collection technique is using accidental sampling technique. Data analysis was performed using multiple linear regression models. The sample is determined using the Slovin formula which is obtained by 48 employees as a sample. Sampling was done using accidental sampling. Data analysis was performed using multiple linear regression models. Based on the simulthan test results, the variable of competence and career have a significant with together effect on the employee performance at the PKS PTPN V Sei Garo Kampar Regency. While based on the partial test results, the variable of competence and career have a significant with individual effect on the employee performance at the PKS PTPN V Sei Garo Kampar Regency, with career as the dominant variable affecting employee performance. The closeness of the relationship that occurs between the atractiveness of competence and career on the employee performance is very strong with a correlation coefficient R of 85,6%. While contribution of competence and career on the employee performance is equual to 72.1% while the remaining 27,9% is influenced by other variables not examined in this study.